Diretor escolar: contribuições de um curso semipresencial para a formação dos diretores ingressantes da rede estadual de ensino de São Paulo - Francisco, Rosangela de Lima (2020)
The constant and rapid changes in the contemporary world require professionals to seek updating and improvement to meet the necessary demands. Thus, like other professionals, school principal face situations in the school environment that mobilize them to seek different solutions, which demand different skills, which he has not always develop. That is why it is essential that he undergoes a process of continuing education that helps him to build new skills to be mobilized in the challenges of the school routine. SEDUC-SP, through the School of Training and Improvement of Professionals of the Education Secretariat “Paulo Renato Costa Souza” (EFAPE), when opening the 2017 public tender, for new directors of the state public network, demanded that those who became effective attend a training course - Specific Training Course for incoming School Principal, to prepare them to face the challenges of the job more efficiently and effectively. The present research, which focuses on this course, intended to verify if it meets the training needs of the school principal, in all its dimensions. Thus, the general objective of the research was to analyze the EFAPE course for incoming principals in terms of their contribution to the formation of the school principal. The incoming director course is semi-presential and the part offered at AVA-EFAPE is self-instructional. The data sources were the interview with four new directors, the records of the directors in the AVA (Virtual learning environment), the course content; legislation and various theoretical references in the field of training, such as Lück (2008, 2009, 2010, 2011), Libâneo et al (2010); and ICT and EAD, such as Almeida (2002, 2004, 2009), Prado (2006, 2009), Levy (1999), Moran (2008), etc. For the analysis of the data, a qualitative approach was chosen and more specifically the 'Análise de Prosa' (Prose Analysis) (André, 1983), which is understood as a way to analyze a content looking for several factors, that is, making all possible information relevant in order to approximate the meaning attributed by the participants and the documents. From the analysis, it was considered that the course has contributed to professional performance and that it fulfills the training objectives. However, evidence was found that suggests other training needs, some of which were mentioned by the directors themselves and others were detected by comparing the testimonies with other documents. The directors did not assume the virtual learning community as a space for interaction, preferring the use of the Whatsapp application which, according to the testimonies, ended up even compensating for the lack of an online tutor, in some situations. Face-to-face meetings also helped to fill this gap, but met many other needs of these directors. It was also detected that there is a greater need for training ICT directors in order to develop new skills that enable them to assume the leadership role in the school and in the community. Finally, it was found that the training must continue so that the director is able to deal with the constant changes, a contemporary world's characteristic